Defensive production of formic acid (80%) by a carabid beetle (Galerita lecontei) - Rossini, Carmen (The National Academy of Sciences of the USA, 1997)
The carabid beetle Galerita lecontei has a pair of abdominal defensive glands that secrete a mixture of formic acid, acetic acid, and lipophilic components (long-chain hydrocarbons and esters). Formic acid, at the concentration of 80%, is the principal constituent. The beetle ejects the secretion as a spray, which it aims accurately toward parts of the body subjected to assault. At full capacity, the glands store 4.5 mg of formic acid (3% of body mass), enough for upward of six ejections. The beetle reloads the glands at a rate of 126 μg of formic acid per day. For the approximately 500 secretory cells of the glands, this means an hourly output of 10 ng of formic acid per cell, or about 5% of cell volume. Replenishing empty glands to their full formic acid load takes the beetle an estimated 37 days. Replenishing the 0.7 mg of formic acid expended in a single discharge takes 5.5 days.